Sorting out “non‐canonical” autophagy - Fracchiolla, Dorotea (EMBO J, 2018)
Canonically, LC3 lipidation has been associated with autophagy pathways but it becomes increasingly clear that this modification can also occur during autophagy‐unrelated processes. In this issue, Florey and colleagues find that the WD40 domain of ATG16L1 is dispensable for LC3 lipidation during starvation‐induced autophagy but required for its lipidation during several other membrane‐based processes that are different from autophagy. This finding opens the door for the analysis of the functions of LC3 lipidation in these pathways.